Kids SIPsmartER: A Feasibility Study to Reduce Sugar-Sweetened Beverage Consumption Among Middle School Youth in Central Appalachia - Lane, Hannah (Am J Health Promot, 2017)
PURPOSE: To test the feasibility of Kids SIPsmartER, a school-based intervention to reduce consumption of sugar-sweetened beverages (SSBs). DESIGN: Matched-contact randomized crossover study with mixed-methods analysis. SETTING: One middle school in rural, Appalachian Virginia. PARTICIPANTS: Seventy-four sixth and seventh graders (5 classrooms) received Kids SIPsmartER in random order over 2 intervention periods. Feasibility outcomes were assessed among 2 teachers. INTERVENTION: Kids SIPsmartER consisted of 6 lessons grounded in the Theory of Planned Behavior, media literacy, and public health literacy and aimed to improve individual SSB behaviors and understanding of media literacy and prevalent regional disparities. The matched-contact intervention promoted physical activity. MEASURES: Beverage Intake Questionnaire-15 (SSB consumption), validated theory questionnaires, feasibility questionnaires (student and teacher), student focus groups, teacher interviews, and process data (eg, attendance). ANALYSIS: Repeated measures analysis of variances across 3 time points, descriptive statistics, and deductive analysis of qualitative data. RESULTS: During the first intervention period, students receiving Kids SIPsmartER (n = 43) significantly reduced SSBs by 11 ounces/day (P = .01) and improved media (P < .001) and public health literacy (P < .01) understanding; however, only media literacy showed between-group differences (P < .01). Students and teachers found Kids SIPsmartER acceptable, in-demand, practical, and implementable within existing resources. CONCLUSION: Kids SIPsmartER is feasible in an underresourced, rural school setting. Results will inform further development and large-scale testing of Kids SIPsmartER to reduce SSBs among rural adolescents.